Dilation or biodegradable stent placement for recurrent benign esophageal strictures: a randomized controlled trial - Walter, Daisy; van den Berg, Maarten W.; Hirdes, Meike M.; Vleggaar, Frank P.; Repici, Alessandro; Deprez, Pierre H.; Viedma, Bartolomé L.; Lovat, Laurence B.; Weusten, Bas L.; Bisschops, Raf; Haidry, Rehan; Ferrara, Elisa; Sanborn, Keith J.; O’Leary, Erin E.; van Hooft, Jeanin E.; Siersema, Peter D. (Endoscopy, 2018)
Background Dilation is the standard of care for recurrent benign esophageal strictures (BES). Biodegradable stents may prolong the effect of dilation and reduce recurrences. Efficacy and safety of dilation and biodegradable stent placement early in the treatment algorithm of recurrent BES were compared.Methods This multicenter, randomized study enrolled patients with BES treated with previous dilations to ≥ 16 mm. The primary end point was number of repeat endoscopic dilations for recurrent stricture within 3 and 6 months. Secondary outcomes through 12 months included safety, time to first dilation for recurrent stricture, dysphagia, and level of activity.Results At 3 months, the biodegradable stent group (n = 32) underwent significantly fewer endoscopic dilations for recurrent stricture compared with the dilation group (n = 34; P < 0.001). By 6 months, the groups were similar. The number of patients experiencing adverse events was similar between the groups. Two patients in the biodegradable stent group died after developing tracheoesophageal fistulas at 95 and 96 days post-placement; no deaths were attributed to the stent. Median time to first dilation of recurrent stricture for the biodegradable stent group was significantly longer (106 vs. 41.5 days; P = 0.003). Dysphagia scores improved for both groups. Patients in the biodegradable stent group had a significantly higher level of activity through 12 months (P < 0.001).Conclusion Biodegradable stent placement is associated with temporary reduction in number of repeat dilations and prolonged time to recurrent dysphagia compared with dilation. Additional studies are needed to better define the exact role of biodegradable stent placement to treat recurrent BES.